Balanced anesthesia with sevoflurane does not alter redox status in patients undergoing surgical procedures - Orosz, Jose Eduardo B. [UNESP]; Braz, Leandro Gobbo [UNESP]; Ferreira, Ana Lúcia dos Anjos [UNESP]; Amorim, Rosa Beatriz [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Yeum, Kyung-Jin; Braz, José Reinaldo Cerqueira [UNESP]; Braz, Mariana Gobbo [UNESP] (Elsevier B.V., 2014)
Despite the effectiveness and safety of anesthetics, some unanswered questions remain concerning their toxicity and effects on cellular redox balance. To test for possible toxic effects of balanced anesthesia maintained with the volatile anesthetic sevoflurane, we evaluated oxidative stress during and after general anesthesia in 15 adult patients without comorbidities who underwent elective minor surgical procedures. Venous blood samples were collected at baseline, before anesthesia (t0); after anesthesia induction and immediately before surgery (t1); 2 h after the beginning of anesthesia (t2); and on the day following surgery (t3). Antioxidant defense was determined by fluorometry. Oxidative stress markers included oxidative DNA damage, evaluated by the alkaline comet assay, and plasma malondialdehyde (MDA), assessed by high performance liquid chromatography (HPLC). No increase in oxidized DNA damage or antioxidant defense was observed. Plasma MDA increased only at t3 compared with t2. Balanced sevoflurane-maintained anesthesia appears neither to damage DNA nor to alter redox status. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Inhalation anesthetics; Genotoxicity test; Oxidative stress; Minor surgery